rastreamento histoquímico, fitoquímico e biológico de folhas de Plinia cauliflora (DC.) Kausel (Myrtaceae) - Souza-Moreira, Tatiana M. [UNESP]; Moreira, Raquel Regina Duarte [UNESP]; Sacramento, Luis V. S. [UNESP]; Pietro, Rosemeire C. L. R. [UNESP] (Springer Nature, 2010)
In this work, chemical and biological activities of crude extracts obtained with 50% ethanol, 70% ethanol, acetone:water (7:3; v/v) and chloroform of Plinia cauliflora (DC.) Kausel, Myrtaceae, leaves, a native tree from several regions of Brazil, was investigated. Histochemical and phytochemical screenings were done according to characterization reactions and thin layer chromatography. To assist in extracts standardization, total phenol and flavonoids content spectrophotometric was performed. Antioxidant activity was analyzed by percentage of radical scavenging using DPPH solution. Antimicrobial activity was evaluated against Gram-positive, Gram-negative pathogenic bacteria and species of Candida using agar diffusion and minimal inhibitory concentration (MIC) determination methods according to standard methods. The leaves presented lipids at secretory cavity and phenols, mainly tannins, in nervures and palisade parenchyma. Polar extracts showed flavonoids, tannins and high content of phenols and flavonoids. The extracts showed great antioxidant activity and antimicrobial activity was better against Candida species than against bacteria.
Histochemical, phytochemical and biological screening of Plinia cauliflora (DC.) Kausel, Myrtaceae, leaves
Keywords: Antimicrobial activity; Antioxidant activity; Chemical screening; Plinia cauliflora; 1,1 diphenyl 2 picrylhydrazyl; acetone; alcohol; chloroform; flavonoid; lipid; phenol; plant extract; Plinia cauliflora extract; scavenger; tannin derivative; unclassified drug; water; agar diffusion; antimicrobial activity; antioxidant activity; biological activity; Candida; controlled study; drug activity; drug screening; Gram negative bacterium; Gram positive bacterium; histochemistry; minimum inhibitory concentration; Myrtaceae; nonhuman; phytochemistry; plant leaf; spectrophotometry; standardization; thin layer chromatography